John and Elaine Steinbeck in Finland. - UAS Saarinen:::Creator::::::::::::
John Steinbeck answering questions from students in the auditorium of the University of Helsinki. Meri Utrio, editor and translator, and Elaine Steinbeck sitting in the front row.